A RETROSPECTIVE REVIEW OF ABDOMINAL HYSTERECTOMY IN A TEACHING HOSPITAL - Acharya, Sarita; Shrestha, Sweety; Pal, M. N. (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Hysterectomy is the most commonly performed gynaecological surgery throughout the world. It may be life saving procedure in acute uterine hemorrhage; whereas improves the quality of life in a patient with certain uterine pathology such as fibroids, endometriosis and uterine prolapse. The objective of this study is to review the indications and complications of abdominal hysterectomy as well as to assess the correlation of preoperative clinical and ultrasonographic diagnosis with histopathology of hysterectomy specimens. MATERIAL AND METHODS: A retrospective review of medical records of patients who underwent abdominal hysterectomy between January 2010 and July 2012 in the College of Medical Sciences Teaching Hospital, Nepal was done. Various demographic and pertinent clinical informations were retrieved. Clinical presentations, indications and complications of the hysterectomy as well as the correlation between the clinical diagnosis, ultrasound findings and histopathological diagnosis of the hysterectomy specimen was studied. RESULTS: Between January 2010 and July 2012 a total of 139 patients had undergone abdominal hysterectomy for various indications. The mean age at the time of hysterectomy was 45.5 years. Abnormal vaginal bleeding and lower abdominal pain were the main presenting complaints. The median duration of symptoms was 12 months. Fourty three (40%) had hysterectomy alone and 96 (60%) had hysterectomy with salpingo oophorectomy. The most common clinical indication for hysterectomy was fibroid uterus (40.3%) followed by benign ovarian tumor (18.7%) and dysfunctional uterine bleeding (17.3%). There were no major postoperative complications. The correlation between clinical diagnosis and histopathology was significant at 0.01 level using Pearson correlations. CONCLUSION: Uterine fibroids and benign ovarian tumors are the common indications for abdominal hysterectomy. Postoperative complications are minimal and most of the time the clinical diagnosis correlates with the postoperative histopathological diagnosis. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Pages 16-19